The Influence of Unionism Upon Earnings: Reply - Ross, A. M. (Quarterly Journal of Economics, 1948)
Journal Article The Influence of Unionism Upon Earnings: Reply Get access A. M. Ross A. M. Ross University of California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 62, Issue 5, November 1948, Pages 787–790, https://doi.org/10.2307/1883473 Published: 01 November 1948